Mini quilts : fresh, fun patterns to quilt in a snap - Davis, Jodie, 1959- (The Taunton Press, 2013)
"This book presents step-by-step instructions for all sorts of wonderful quilt techniques to sample and experience quilting satisfaction. Each mini quilt is a worthwhile project on its own, a way to use leftover scraps or fabric stash, and can also be used as a component in a larger project"--